GOVERNANCE OF THE INTERNET OF THINGS - Trautman, Lawrence J; Hussein, Mohammed T; Ngamassi, Louis; Molesky, Mason J (Jurimetrics (Chicago, Ill.), 2020)
Today's increasing rate of technological change results from the rapid growth in computer processing speed, when combined with the cost decline of processing capacity, and is of historical import. The daily life of billions of individuals worldwide has been forever changed by technology in just the last few years. Costly data breaches continue at an alarming rate. The challenge facing humans as they attempt to govern the process of artificial intelligence, machine learning, and the impact of billions of sensory devices connected to the Internet is the subject of this Article.